(untitled) (World Bulletin of Management and Law, 2022)
The present research has investigated the effect of the failure of corporate governance mechanisms on the financial distress of companies listed on the stock exchange of Iraq. This research is of an applied type, the purpose of which is to answer the question that what is the effect of failure of corporate governance mechanisms on the financial helplessness of companies admitted to the stock exchange of Iraq? The research community is all the companies that are members of the Iraq Stock Exchange, which were selected by using sampling with the method of systematic exclusion of 35 companies from the companies accepted in the Tehran Stock Exchange during the period of 2020-214 and using The combined data and generalized least squares regression method of the .desired hypotheses were tested in the research